INNOVATION MANAGEMENT IN UNIVERSITIES AND FEDERAL INSTITUTES OF THE NORTHEAST: REFLECTIONS OF ADMISSION TO THE PROFNIT MASTER'S PROGRAM IN INTELLECTUAL PROPERTY - Pereira, Jonas Marques (2022)
Technological innovation, through scientific research, promotes access to knowledge, especially in higher education institutions, which need mechanisms that promote innovative actions and manage the knowledge produced. This study sought, through descriptive, bibliographic, and documentary research, to highlight the importance of PROFNIT within the universities and federal institutes of the Northeast. Data obtained on the websites of the researched institutions and on the website of the National Institute of Industrial Property (INPI) were analyzed, demonstrating their relevance in scientific production with the technological innovation centers (TICs) and intellectual property management. The results allowed us to observe that the participation of universities and federal institutes in the PROFNIT master's program was closely related to the number of patent deposits registered by the institutions in the years that followed after joining the program, representing an advance in the valorization of the protection of production science in these institutions.